2014
DOI: 10.1159/000360477
|View full text |Cite
|
Sign up to set email alerts
|

The Role of B Regulatory Cells and Semaphorin3A in Atopic Diseases

Abstract: When the pathogenesis of allergic inflammatory diseases such as asthma, allergic rhinitis and atopic dermatitis is discussed, one should take into consideration the involvement of regulatory cells/molecules whose role is to prevent the induction and/or deterioration of such diseases. The involvement of T regulatory cells and FoxPp3 is well established in asthma, but only little is known about the involvement of B regulatory cells (Bregs) and the soluble regulatory molecule semaphorin3A (sema3A) in atopic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…We targeted known transcription factor or regulatory effector molecule transcripts to determine expression in peripheral blood from endemic control, asymptomatic and symptomatic L. infantum -infected dogs. We selected genes associated with regulatory B cells (38, 39), immune exhaustion (2, 40, 41), B cell associated/regulatory transcription factors (17, 23, 42). Regulatory B cell marker stim2 was decreased compared to IgD lo B cell controls (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We targeted known transcription factor or regulatory effector molecule transcripts to determine expression in peripheral blood from endemic control, asymptomatic and symptomatic L. infantum -infected dogs. We selected genes associated with regulatory B cells (38, 39), immune exhaustion (2, 40, 41), B cell associated/regulatory transcription factors (17, 23, 42). Regulatory B cell marker stim2 was decreased compared to IgD lo B cell controls (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TSP1 + B cells play an important role in the maintenance of the homeostasis in the body [ 2 , 3 ]. Published data indicate that the reduced number or the functional compromise of TSP1 + cell is associated with a number of immune disorders, such as allergic asthma [ 4 ], food allergy [ 5 ], and some other atopic diseases [ 6 ]. Factors or mechanisms leading to TSP1 + cell dysfunction are not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis by Stelmaszczyk-Emmel et al ] found significantly fewer T-regs (as a percentage of all CD4þ cells) in children with atopic dermatitis and/or food allergy when compared with healthy controls, as well as a significant negative correlation between serum IgE levels and T-regs. Moreover, coculture of B-regs with T-regs enhanced T-reg properties via FoxP3 upregulation [20]. However, they also found significantly higher FoxP3 expression, a transcription factor responsible for maturation of T-regs in the thymus and maintenance of their immunosuppressive function, in allergic individuals when compared with healthy controls.…”
Section: Key Pointsmentioning
confidence: 98%
“…Recent research has also been investigating the role of regulatory T cells (T-regs) and B cells (B-regs), both of which are high in nonallergic individuals, in the pathogenesis of allergic disease [20]. A recent analysis by Stelmaszczyk-Emmel et al ] found significantly fewer T-regs (as a percentage of all CD4þ cells) in children with atopic dermatitis and/or food allergy when compared with healthy controls, as well as a significant negative correlation between serum IgE levels and T-regs.…”
Section: Key Pointsmentioning
confidence: 99%